MODERNISASI ALAT TANGKAP MASYARAKAT NELAYAN DI DESA BONGO 1979-2005 - Resmiyati Yunus; Ainun Mokoagow; Sintia Pakaya (Universitas Negeri Gorontalo, 2021)
This study aims to determine how the modernization of fishing gear in the fishing community of Bongo Village 1979-2005. By using the historical research method, it begins with source collection (Heuristics), continues with source criticism which has two parts, namely Internal and External criticism, then continues with interpretation which is source analysis and closes with historiography, namely historical writing. This study describes how to modernize fishing gear in Bongo Village.